Development of a resource-saving technology for the treatment of ferrum-containing wastewater from etching operations - Yatskov, Mykola; Korchyk, Natalia; Budenkova, Nadia; Mysina, Oksana (Eastern-European journal of enterprise technologies, 2022)
The object of this study is wastewater from chloride and sulfate etching operations. This paper reports results of research on ways to reduce the consumption of chemical reagents in wastewater treatment systems from etching operations. Spent etching solutions are subject to regeneration with return to the production process and partial dosing to the main stream of wastewater. It was found that at a ferrum concentration of 30 g/l in etching solutions, the solution must be treated with an alkaline reagent (10–20 % NaOH) to pH=3.5–4.0 in order to return to the technological process. In this case, the final concentration of ferrum is 11 g/l. The use of hydrogen peroxide (20–40 % H2O2) together with the alkaline reagent makes it possible to increase the degree of extraction by 30 %, that is, the final concentration of ferrum is 8 g/l. When discharging 1 m3 of etching solutions, 0.5 m3 is subject to regeneration and, after mixing with 0.5 m3 of the commercial reagent (HCl) it returns to the technological process. Commercial acid consumption is reduced by 50 %. It was shown that the use of individual flows of waste solutions as a chemical reagent reduces the cost of reagents for their neutralization (saving alkaline reagent is 80 %). Thus, 1.2 kg/m3 of a commercially available reagent (NaOH) is consumed per 1 m3 of solutions (etching and degreasing) after mixing them, and, without mutual neutralization, this consumption is 6 kg/m3. To neutralize etching solutions, it is recommended to carry out the process in the range of pH=6.5–7.5. For a solution in which Fe3+ ions predominate with an initial concentration of 0.53 mol/L, a degree of extraction of 0.9 is achieved, and the total consumption of the reagent (7.1 mol/l) exceeds the stoichiometric one by only 10 %. Deep purification from ferrum-containing impurities using a magnetic device expands the possibilities of practical implementation of further desalting with inverse osmosis. Об’єктом дослідження є стічні води від операцій хлоридного та сульфатного травлення. Представлені результати досліджень шляхів зменшення витрат хімічних реагентів в системах очищення стічних вод від операцій травлення. Відпрацьовані травильні розчини підлягають регенерації з поверненням у виробничий процес та частковим дозуванням в основний потік стічних вод. Встановлено, що при концентрації феруму 30 г/л у травильних розчинах з метою повернення в технологічний процес розчин підлягає обробці лужним реагентом (10–20 % NaOH) до рН=3,5–4,0. При цьому кінцева концентрація феруму складає 11 г/л. Застосування гідроген пероксиду (20–40 % Н2О2) разом з лужним реагентом дозволяє збільшити ступінь вилучення на 30 %, тобто кінцева концентрація феруму складає 8 г/л. При скиді 1 м3 травильних розчинів 0,5 м3 підлягає регенерації і після змішування з 0,5 м3 товарного реагенту (HCl) повертається у технологічний процес. Витрата товарної кислоти зменшується на 50 %. Показано, що використання як хімічного реагенту окремих потоків відпрацьованих розчинів дозволяє зменшити витрати реагентів для їх знешкодження (економія лужного реагенту складає 80 %). Так, на 1 м3 розчинів (травлення та знежирення) після їх змішування витрачається 1,2 кг/м3 товарного реагенту (NaOH), а без взаємного знешкодження ця витрата складає 6 кг/м3. Для знешкодження розчинів травлення рекомендовано проводити процес в інтервалі рН=6,5–7,5. Для розчину, в якому переважать йони Fe3+ з початковою концентрацією 0,53 моль/л досягається ступінь вилучення 0,9, а загальна витрата реагенту (7,1 моль/л) перевищує стехіометричну тільки на 10 %. Глибоке очищення від ферумовмісних домішок із застосуванням магнітного пристрою розширює можливості практичної реалізації подальшого знесолення оберненим осмосом